1985
DOI: 10.1017/s0043174500083119
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Weed Control After Repeat Applications of Thiocarbamate and Other Herbicides

Abstract: Of 17 thiocarbamate herbicides tested in the greenhouse in repeat soil applications made 4 to 16 weeks apart, 9 showed definite losses in herbicidal activity after the second application. Those showing reduced activity included EPTC (S-ethyl dipropylthiocarbamate), vernolate (S-propyl dipropylthiocarbamate), and butylate (S-ethyl diisobutylthiocarbamate), which have been reported previously to develop accelerated breakdown, plus R-15574 (S-benzyl dipropylthiocarbamate and the sulfoxides of EPTC, vernolate, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
1
19
1
Order By: Relevance
“…It has been widely reported that soil microbes evolve the ability of rapid degradation of many xenobiotic compounds including pesticides, fungicides, and herbicides, which were synthesized by human and did not exist previously in soils. For example, biodegradations of herbicide 2,4-dichlorophenoxy and nematicide fenamiphos are faster in soils previously experienced these chemicals than in naïve soils [21,25,26]. In this study, we hypothesized that naïve soil microbes may evolve the ability to degrade allelochemicals of invasive plants (natural products) more rapidly compared with the human-synthesized xenobiotic compounds and that the ability may increase with increasing invasion time.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that soil microbes evolve the ability of rapid degradation of many xenobiotic compounds including pesticides, fungicides, and herbicides, which were synthesized by human and did not exist previously in soils. For example, biodegradations of herbicide 2,4-dichlorophenoxy and nematicide fenamiphos are faster in soils previously experienced these chemicals than in naïve soils [21,25,26]. In this study, we hypothesized that naïve soil microbes may evolve the ability to degrade allelochemicals of invasive plants (natural products) more rapidly compared with the human-synthesized xenobiotic compounds and that the ability may increase with increasing invasion time.…”
Section: Introductionmentioning
confidence: 99%
“…Many soil-applied pesticides are degraded more rapidly following repeated application at the same site (Kaufman 1987;Racke and Coats 1990). Several herbicides are prone to this phenomenon of enhanced degradation, including members of the thiocarbamate group, the ureas, linuron and monolinuron, the amides, propyzamide and napropamide, and the triazinones, chloridazon and metamitron (Engvild and Jensen 1969;Gray and Joo 1985;Roeth 1986;Walker and Welch 1991;Roberts et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Cotterill & Owen, 1989). Gray & Joo (1985) used a glasshouse test to evaluate the extent to which weed control performance of a number of soil-applied herbicides was affected by repeated application. They examined 17 thiocarbamates of which nine showed reduced activity after the second soil treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Tlie present experiments were made to investigate further the possibility of enhanced degradation of some soil-applied herbicides. In response to the results of Gray & Joo (1985), the compounds chosen included propyzamide, napropamide and alachlor. Representative triazine and urea herbicides were also studied since these chemical groups include some of the more important soil-applied herbicides used in the U.K.…”
Section: Introductionmentioning
confidence: 99%